2000
DOI: 10.1074/jbc.m005714200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Catalytic Active Site in the Latent and Active Natural Gelatinase B from Human Neutrophils

Abstract: Matrix metalloproteinases are endopeptidases that have a leading role in the catabolism of the macromolecular components of the extracellular matrix in a variety of normal and pathological processes. Human gelatinase B is a zinc-dependent proteinase and a member of the matrix metalloproteinase family that is involved in inflammation, tissue remodeling, and cancer. We have conducted x-ray absorption spectroscopy, atomic emission, and quantum mechanics studies of natural and activated human gelatinase B. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
(41 reference statements)
6
20
0
Order By: Relevance
“…5 demonstrates the feasibility of NAC docking at MMP-9's active-site Zn molecule. This premise is supported by the studies of Kleifeld et al, who clarified the nature of MMP-9 activation, i.e., the latent Zn binding site becomes catalytically competent by dissociation of the thiol propeptide from the Zn atom [30]. Although our data suggest a plausible MMP-9 inhibitory mechanism, in order to provide conclusive evidence for GSH's and NAC's interactions with MMP-9's active site, it is necessary to conduct quantitative biophysics.…”
Section: Discussionsupporting
confidence: 67%
“…5 demonstrates the feasibility of NAC docking at MMP-9's active-site Zn molecule. This premise is supported by the studies of Kleifeld et al, who clarified the nature of MMP-9 activation, i.e., the latent Zn binding site becomes catalytically competent by dissociation of the thiol propeptide from the Zn atom [30]. Although our data suggest a plausible MMP-9 inhibitory mechanism, in order to provide conclusive evidence for GSH's and NAC's interactions with MMP-9's active site, it is necessary to conduct quantitative biophysics.…”
Section: Discussionsupporting
confidence: 67%
“…Because of the ability to degrade the major component of the ECM and basement membrane, its overexpression facilitates the metastatic spread [11]. Growth factors (TGF␣, TGF␀, TNF␣, EGF), cytokines (interleukin 1 and 4), and hormones (progesterone, retinoids) are responsible for the pre-translational control of MMP9 expression [11,12]. At the post-translational level, all MMPs are under the control of specific tissue inhibitors of metalloproteinases (TIMPs) that bind in proximity of the catalytic domain of MMPs, preventing substrate attachment [13].…”
Section: Introductionmentioning
confidence: 99%
“…The zinc-protein ratio was further investigated by XAS edge step analysis following previous procedures (32). Briefly, the edge step of the XAS coefficient should be proportional to the concentration of the absorbing element.…”
Section: The Zinc Stoichiometry In the Fullmentioning
confidence: 99%
“…4, although we carried out energy minimizations with both stereoisomers. (32) suggest that full-length intact MMPs (for the ones tested) contain a single zinc ion, while truncated enzymes (lacking the C-terminal domain) contain two zinc ions. In addition, it was suggested that the zinc content in MMPs might be dependent on the procedure used for enzyme purification (32,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation